The History and Challenges of Women in Genetics: A Focus on Non-Western Women - Elbardisy, Hadeel; Abedalthagafi, Malak (Frontiers in Genetics, 2021)
“Women in much of the world lack support for fundamental functions of a human life”. This truthful portrait was pointed out by Martha Nussbaum in her book “Introduction: Feminism & International Development”. Throughout history, gender inequality has been persistent in many aspects of life, including health and empowerment. Unfortunately, this inequality has not been excluded from the field of science. Perpetual assumption that women’s absence or restriction to secondary roles in various disciplines is an acceptable law of nature misrepresents women's contribution to science and maintains hurdles for participation in the future. According to a recent UNESCO’s report, women make up only 30% of researchers worldwide. But despite all the obstacles, women made major contributions with discoveries that shaped the progress in many scientific fields. In the field of genetics, Rosalind Franklin is an example of unwittingly compromised women’s scientific achievements. Franklin was an expert in X-ray crystallography; her data, especially the “photo 51”, was critical to James Watson and Francis Crick along with their own data to publish the discovery of the double helix DNA structure in 1953. Her contribution was acknowledged posthumously in Watson’s memoir in 1968. Barbara McClintock was a 20th century American cytogeneticist who remains up to date the only woman receiving an unshared Nobel prize in Physiology or Medicine. McClintock dedicated her work to cytogenetics and discovered the phenomenon of mobile genes. Her research was initially subjected to skepticism in the 1950s. It was not until the late 1960s that the community realized the significance of McClintock’s discovery. The history of science is occupied with a myriad of similar tales of such inspiring women that, after tremendous struggles, thrived and achieved breakthroughs in their respective fields. It is prominent our limited knowledge of women’s experience and struggle in science in non-western world. Addressing the stories of this outstanding minority is critical to expand the understanding of the gender disparity factors embedded in diverse cultures. In this article, we attempt to put the spotlight on some fascinating non-western women and their significant contributions to the field of genetics.